2023
DOI: 10.12771/emj.2023.e12
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Etiology of Elbow Pain Based on the Healthcare Bigdata Hub in Korea: A Longitudinal Observational Study

Hyungsuk Kim,
Taeyang Jang

Abstract: This study investigated the epidemiological and etiological trends associated with elbow pain over the past decade in South Korea. Methods: Nationwide health statistics data from 2011 to 2020 pertaining to elbow pain-related diseases and soft tissue damages were sourced from the Healthcare Bigdata Hub with disease codes M771 (lateral epicondylitis), M770 (medial epicondylitis), S53 (elbow injury, dislocation, sprain), and G56 (mononeuropathies of the upper limb). The study assessed the annual fluctuations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Dr. Youngbok Kim [8] states in his editorial that "this compilation of papers, encompassing a series of domestic epidemiological studies on elbow diseases, distinguishing factors for elbow pain, conservative and surgical treatments, and postoperative rehabilitation, is noteworthy as it provides a comprehensive overview of the understanding and treatment of elbow diseases." Big data analysis also revealed that the prevalence of diseases causing elbow pain was 114.21 per 100,000 for lateral epicondylitis, 32.82 for medial epicondylitis, 61.46 for elbow injury, dislocation, and sprain, and 39.15 for mononeuropathy of the upper limb [9]. The diagnosis, treatment, and rehabilitation of patients with elbow pain disorders will provide current and high-quality information for both specialists and general practitioners.…”
Section: In This Issuementioning
confidence: 99%
“…Dr. Youngbok Kim [8] states in his editorial that "this compilation of papers, encompassing a series of domestic epidemiological studies on elbow diseases, distinguishing factors for elbow pain, conservative and surgical treatments, and postoperative rehabilitation, is noteworthy as it provides a comprehensive overview of the understanding and treatment of elbow diseases." Big data analysis also revealed that the prevalence of diseases causing elbow pain was 114.21 per 100,000 for lateral epicondylitis, 32.82 for medial epicondylitis, 61.46 for elbow injury, dislocation, and sprain, and 39.15 for mononeuropathy of the upper limb [9]. The diagnosis, treatment, and rehabilitation of patients with elbow pain disorders will provide current and high-quality information for both specialists and general practitioners.…”
Section: In This Issuementioning
confidence: 99%